Microglia in the TBI Brain: The Good, The Bad, And The Dysregulated - Loane, David J. (Exp Neurol, 2015)
As the major cellular component of the innate immune system in the central nervous system (CNS) and the first line of defense whenever injury or disease occurs, microglia play a critical role in neuroinflammation following a traumatic brain injury (TBI). In the injured brain microglia can produce neuroprotective factors, clear cellular debris and orchestrate neurorestorative processes that are beneficial for neurological recovery after TBI. However, microglia can also become dysregulated and can produce high levels of pro-inflammatory and cytotoxic mediators that hinder CNS repair and contribute to neuronal dysfunction and cell death. The dual role of microglial activation in promoting beneficial and detrimental effects on neurons may be accounted for by their polarization state and functional responses after injury. In this review article we discuss emerging research on microglial activation phenotypes in the context of acute brain injury, and the potential role of microglia in phenotype-specific neurotrestorative processes such as neurogenesis, angiogenesis, olgogendrogenesis and regeneration. We also describe some of the known molecular mechanisms that regulate phenotype switching, and highlight new therapeutic approaches that alter microglial activation state balance to enhance long-term functional recovery after TBI. An improved understanding of the regulatory mechanisms that control microglial phenotypic shifts may advance our knowledge of post-injury recovery and repair, and provide opportunities for the development of novel therapeutic strategies for TBI.